Learned Helplessness and its Relationship to Exam Anxiety Among Students with Learning Disability in Tafila Governorate - Al-Najadat, Hussain Matrouk; Al-Saud, Othman AbdulQader (Journal of Educational and Psychological Sciences, 2022)
This study aimed to investigate the relationship between learned helplessness and exam anxiety among students with learning disabilities in the Tafila Governorate. To achieve the study purposes, the two instruments (learned helplessness and exam anxiety) were developed to collect the data. The instruments' psychometric properties (validity and reliability) were checked; then, the instruments were applied on a sample consisted of (495) male and female students with learning disabilities, who were chosen randomly in the Tafila Governorate. The results of the study showed the level of learned helplessness and exam anxiety among the study participants were moderate. The results also indicated that there was a statistically significant relationship at the level of (α≤0.05) between the learned helplessness and exam anxiety. In addition, the results showed that there were no statistically significant differences at the level of (α≤0.05) in the level of learned helplessness among students according to their gender where the results showed significant differences at the level of (α≤0.05)) in the level of exam anxiety among students according to their gender in favor of male students. The study recommended designing counseling programs for parents and teachers to work on alleviating exam anxiety and learned helplessness among students with learning disabilities.
Keywords: Learned Helplessness; Test Anxiety; Learning Disabilities